Key Molecular Mechanisms of Chaiqinchengqi Decoction in Alleviating the Pulmonary Albumin Leakage Caused by Endotoxemia in Severe Acute Pancreatitis Rats. (19th June 2016) - Wu, Wei; Luo, Ruijie; Lin, Ziqi; Xia, Qing; Xue, Ping
Abstract : To reveal the key molecular mechanisms of Chaiqinchengqi decoction (CQCQD) in alleviating the pulmonary albumin leakage caused by endotoxemia in severe acute pancreatitis (SAP) rats. Rats models of SAP endotoxemia-induced acute lung injury were established, the studies in vivo provided the important evidences that the therapy of CQCQD significantly ameliorated the increases in plasma levels of lipopolysaccharide (LPS), sCd14, and Lbp, the elevation of serum amylase level, the enhancements of systemic and pulmonary albumin leakage, and the depravation of airways indicators, thus improving respiratory dysfunction and also pancreatic and pulmonary histopathological changes. According to the analyses of rats pulmonary tissue microarray and protein-protein interaction network, c-Fos, c-Src, and p85 α were predicted as the target proteins for CQCQD in alleviating pulmonary albumin leakage. To confirm these predictions, human umbilical vein endothelial cells were employed in in vitro studies, which provide the evidences that (1) LPS-induced paracellular leakage and proinflammatory cytokines release were suppressed by pretreatment with inhibitors of c-Src (PP1) or PI3K (LY294002) or by transfection with siRNAs of c-Fos; (2) fortunately, CQCQD imitated the actions of these selective inhibitions agents to inhibit LPS-induced high expressions of p-Src, p-p85 α, and c-Fos, therefore attenuating paracellular leakage and proinflammatory cytokines release.